MECHANICAL AND PHYSICAL PROPERTIES OF FLY ASH-GGBFS GEOPOLYMER MORTAR FOR IN-SITU APPLICATION - Mohd Zin @ Nordin, Muhamad Adam (Universiti Teknologi PETRONAS, 2018)
Geopolymer is a relatively new alternative binder for making concrete in construction industry. Use of geopolymer eventually can reduce environmental problems since geopolymer binders are produced from industrial by-products such as fly ash and Grand Granulated Blast Furnace Slag (GGBFS) instead of Ordinary Poland Cement (OPC). However, geopolymer need to cure at elevated temperature which make it be impractical for cast-in situ application due to energy intensive process. Geopolymer need high temperature during curing to accelerate the reaction which otherwise takes long time when curing at ambient condition (20oC – 23o C). This is considered for slow rate in early strength development when curing at ambient temperature. In this work, fly ash and GGBFS were utilized to produce ambient cure geopolymer mortars at different percentage replacement of GGBFS varying from 0% to 50%.